Serio ludere Homenaje a Jean-Pierre Étienvre - Mestre Zaragozá, Marina; Rabaté, Philippe (Collection de la Casa de Velázquez, 2022)
Jean-Pierre Étienvre, author of now classic studies on the Spanish Golden Age, has trained several generations of Hispanists since the prestigious Chair of Golden Age Literature at the Sorbonne, where he is now Professor Emeritus. This tribute volume traces his concerns and interests during his long scientific career through the contributions of numerous colleagues, major figures in French and international Hispanism, and his former students and doctoral candidates.